2015
DOI: 10.1002/ijch.201400192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pre‐annealing on Firing Stability of Atomic Layer‐Deposited Al2O3

Abstract: Al2O3 layers fabricated with atomic layer deposition (ALD) show high levels of surface passivation on p‐ and n‐type silicon wafers. In order to form front and rear electrodes, Al2O3 layers should undergo a firing process at a high peak temperature. Therefore, the Al2O3 layer must be stable under these conditions to maintain a high level of surface passivation during the firing process. In this study, Al2O3 layers fabricated with ALD were pre‐annealed to enhance their thermal stability during the firing process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…By comparing these results, it is observed that the Al 2 O 3 film shows increased negative fixed charge after the heat treatment. Similar results were reported in many papers [19][20][21][22][23]. According to these, the negative fixed charge of Al 2 O 3 results from its structural change.…”
Section: Analysis Of Al 2 O 3 Structuresupporting
confidence: 90%
“…By comparing these results, it is observed that the Al 2 O 3 film shows increased negative fixed charge after the heat treatment. Similar results were reported in many papers [19][20][21][22][23]. According to these, the negative fixed charge of Al 2 O 3 results from its structural change.…”
Section: Analysis Of Al 2 O 3 Structuresupporting
confidence: 90%